Marketing R&D Cooperation as a Mediator Between Customer Relationship Orientation, Digital Banking Orientation, and Marketing Performance at bank BJB - Megantara, Khandinar Shidik; Hurriyati, Ratih; Hendrayati, Heny; Sultan, Mokh. Adib (Universitas Dharma Wacana, 2025)
This study investigates how Customer Relationship Orientation (CRO) and Digital Banking Orientation (DBO) affect Marketing Performance (MP) through the mediating role of Marketing Research and Development Cooperation (MRDC) at Bank BJB. The population consisted of 1,762 marketing and R&D employees in Indonesia, with 316 respondents selected using proportional random sampling. Data were analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that both CRO and DBO significantly influence MRDC, which in turn mediates their effect on MP. Among the dimensions, Strategic Digital Commitment had the strongest contribution within DBO, while the technology aspect was dominant in CRO. These findings highlight the critical role of marketing–R&D collaboration and digital integration to increase marketing performance. The study offers practical implications for managers to strengthen digital-based strategies, improve product/service innovation, and enhance customer engagement. It also provides theoretical contributions by linking relationship orientation, digital orientation, and R&D cooperation in the banking sector, and also giving suggestion on directions for future research.